KOMUNIKASI INTERPERSONAL DAN MOTIVASI BELAJAR (Studi tentang Hubungan Komunikasi Interpersonal Guru-Siswa dan Orangtua-Siswa dengan Motivasi Belajar Siswa SMA Kristen 1 Sragen) - Siswanta, Prasetyo Hari Pamilih, Nurnawati Hindra & (Transformasi, 2017)
The purpose of this research was to determine the effect of interpersonal communicationof teachers and students as well as parents of students on the students motivation SMA Kristen 1Sragen. This type of research is explanatory research. The research location Christian HighSchool 1 Sragen. The study population was the students of class IX and X SMA Kristen 1 Sragentotaling 42 students in which the whole is used as a sample with a total sampling technique. Thetype of data using primary data and secondary data. Data analysis used multiple linearregression. The results showed that there was a relationship of teachers and studentsinterpersonal communication with students' motivation. There was a relationship interpersonalcommunication parents and students with student motivationKey words: interpersonal communication and motivation to learn